Analysis on nasal airway by using scale-adaptive simulation combined with standard k – ω model and 3D printing modeling physical experiment. Issue 4 (July 2019) - Zhan, Jiemin; Xi, Yangyang; Lin, Kay; Yu, Weiguang; Hu, Wenqing
Highlights: A three-dimensional (3D) model of the human upper respiratory tract was reconstructed based on computed tomography medical images. An experimental device of the upper respiratory tract was made by using 3D printing technology. A respiratory experiment is implemented and a scale-adaptive k–ω model is applied for numerical simulation. An airflow shear effect between the nasopharynx and the nasal valve was large, and vortex line separation occurred in the middle and upper nasal tract during the respiratory process. Abstract: The physiological structure of the upper respiratory tract is complex and varies with each individual, and the circulating air has turbulent performance. In this paper, based on computed tomography (CT) medical images published online and the three-dimensional (3D) printing technology, a 3D model of the human upper respiratory tract was reconstructed and an experimental device of the upper respiratory tract was made. We implemented the respiratory experiment and measured the flow rate, and a scale-adaptive k–ω model is applied for numerical simulation, the results are in good agreement. The flow field during respiratory was analyzed by coronal velocity cross section, vortex line and particle tracks. We found that the relatively strong shear effect happens at the areas of nasal valve and nasopharynx. In the middle and upper nasal tract, vortex line separation occurs and there is significant passage effect. The results indicate that SAS method is effective in studying upper respiratory airflow.